1986
DOI: 10.1210/jcem-62-5-915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Luteinizing Hormone/Human Chorionic Gonadotropin-Stimulable Adenylyl Cyclase Activity in Rat Luteal Membranes by Nonsteroidal Component(s) in Human Follicular Fluid*

Abstract: We examined the ability of nonsteroidal components of human follicular fluid (hFF) to alter gonadotropin responsiveness using the LH/hCG-sensitive adenylyl cyclase system of rat luteal membranes. Follicular aspirates were obtained from regularly ovulatory women (n = 10) whose follicles were stimulated by human menopausal gonadotropin and hCG as part of an in vitro fertilization program. hFF from large follicles was pooled and extracted with 10% (wt/vol) activated charcoal. Maximal hCG stimulation of adenylyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…These physicochemical properties might be similar to those of inhibitors reported by other investigators (8,9,13,15,16). These physicochemical properties might be similar to those of inhibitors reported by other investigators (8,9,13,15,16).…”
Section: Biological Activity Of the Mq-lhbi Fractionsupporting
confidence: 90%
See 2 more Smart Citations
“…These physicochemical properties might be similar to those of inhibitors reported by other investigators (8,9,13,15,16). These physicochemical properties might be similar to those of inhibitors reported by other investigators (8,9,13,15,16).…”
Section: Biological Activity Of the Mq-lhbi Fractionsupporting
confidence: 90%
“…In this study, we had similar results, with unfractionated porcine follicular fluids inhibiting [12,I]hLH binding in a dose-dependent manner. On the other hand, Rojas et al (16) have reported that a low molecular weight non-steroidal component of human follicular fluid in¬ hibits LH/hCG binding to rat luteal membranes. On the other hand, Rojas et al (16) have reported that a low molecular weight non-steroidal component of human follicular fluid in¬ hibits LH/hCG binding to rat luteal membranes.…”
Section: Biological Activity Of the Mq-lhbi Fractionmentioning
confidence: 99%
See 1 more Smart Citation